Integrated metabolomic and transcriptomic analysis of Pogostemon cablin shed new light on the complete biosynthesis pathway of pogostone - Wang, Sen; Zeng, Zhaoqi; Zhang, Qi; Liu, Wenhua; Liu, Qinjian; Xie, Chong; Bei, Jinlong; Chen, Bingxian; Zhang, Aixia (Frontiers in Plant Science, 2025)
Pogostemon cablin (patchouli) is a well-known perennial herbaceous plant for traditional Chinese medicine, and its primary bioactive compounds are patchoulol and pogostone. The biosynthesis pathway of patchouli has been well resolved early, while the biosynthesis pathway of pogostone is still not fully resolved due to the lack of terminal enzyme directly synthesizing pogostone. Here, the present study aims to predict the terminal enzyme of pogostone biosynthesis and reconstruct its most possible complete biosynthesis, through the integrated transcriptomic and metabolomic analysis. The metabolomic and transcriptomic profiles of patchouli leaf were largely different to those of root and stem. Patchoulol analogs like patchoulene and germacrene mainly accumulated in leaf, while pogostone content was much higher in root. Based on the integrated analysis of differentially expressed genes and metabolites, we reconstructed the biosynthesis pathways of patchoulol, and predicted the most likely complete biosynthesis pathway of pogostone. Besides, we identified 29 highly-expressed genes involved in pogostone biosynthesis for the neo-octoploid genome of patchouli, and most of their expression levels were strongly correlated with pogostone content. In particular, patchouli BAHD-DCR acyltransferases (BAHD-DCRs) were phylogenetically distant from but structurally similar to the other known plant BAHD acyltransferases. Most of them possessed the conservative catalysis motif HXXXD, and the catalysis center could bind to the widely recognized substrate molecules of 4-hydroxy-6-methyl-2-pyrone and 4-methylvaleryl-CoA and product molecule of pogostone. Thus, the highly-expressed BAHD-DCRs in patchouli root were proposed to be terminal enzymes directly synthesizing pogostone. The findings here provide more supporting evidence for the medical use of patchouli whole plants, and make an important step forward fully resolving the pogostone biosynthesis pathway. The identified genes involved in pogostone biosynthesis, especially BAHD-DCRs, deserve further investigation and utilization in the synthetic production of pogostone.